A Target Situation Analysis of the Requirements of English Language Competence for Arabic Airlines Ground Staff - Alshayban, Abdullah (Journal of English Language Teaching and Applied Linguistics, 2026)
The study explores the English Language needs of Arabic Airline ground staff in specialized contexts, focusing mainly on routine communication with passengers. The study conducted a Target Situation Linguistics Analysis to investigate the staff’s communicative requirements, competence, and weaknesses. Mixed-methods research was used to conduct the data collection and analysis procedures. The data analysis procedure followed two phases of data collection. First, the data collection was conducted through a structured questionnaire based on the English language: 1) speaking, listening, reading, and writing, 2) communication skills, such as inquiry, persuasion, active listening, and intelligibility, and 3) English vocabulary for specific purposes. Second, the English language skills of the participants were evaluated by the British Council English Score’s Core Skills and Speaking tests. The findings revealed that a significant number of the participants possessed inadequate or sub-par proficiency levels, making it consistent with the findings of other research in different contexts. For example, Ling and Wimolkasem (2022) reached similar results in China and Thailand. Moreover, the findings underscore the need for better-tailored teaching programs and modules to account for the diversity within learners, in this case, the ground aviation staff. It also adds valuable insights for curriculum developers and teachers in different professional contexts. The study found there is a critical need to introduce tailored programs for aviation staff that would incorporate effective adult communication strategies, enabling them to communicate effectively in linguistically diverse environments.